Device Performance of Emerging Photovoltaic Materials (Version 3). Issue 1 (9th December 2022) - Almora, Osbel; Baran, Derya; Bazan, Guillermo C.; Cabrera, Carlos I.; Erten‐Ela, Sule; Forberich, Karen; Guo, Fei; Hauch, Jens; Ho‐Baillie, Anita W. Y.; Jacobsson, T. Jesper; Janssen, Rene A. J.; Kirchartz, Thomas; et al.
Abstract: Following the 2nd release of the "Emerging PV reports, " the best achievements in the performance of emerging photovoltaic devices in diverse emerging photovoltaic research subjects are summarized, as reported in peer‐reviewed articles in academic journals since August 2021. Updated graphs, tables, and analyses are provided with several performance parameters, e.g., power conversion efficiency, open‐circuit voltage, short‐circuit current density, fill factor, light utilization efficiency, and stability test energy yield. These parameters are presented as a function of the photovoltaic bandgap energy and the average visible transmittance for each technology and application, and are put into perspective using, e.g., the detailed balance efficiency limit. The 3rd installment of the "Emerging PV reports" extends the scope toward triple junction solar cells. Abstract : The 3rd installment of the "Emerging PV reports" continues presenting and analyzing the best research achievements in the performance of emerging single‐junction and monolithic multijunction solar cells, as reported in peer‐reviewed articles in academic journals since August 2021. In this installment, for the first time, AgBiS2 and triple junction cells are considered.